2011
DOI: 10.1007/s13197-010-0224-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple fortification on the bioavailability of minerals in wheat meal bread

Abstract: Bioavailability of calcium, iron and zinc as calcium carbonate (CaCO3), ferrous sulfate (FeSO4) and zinc sulphate (ZnSO4) @ 1,000, 40 and 20 mg kg(-1) respectively from fortified bread of 72% extraction straight grade flour was assessed. Fortified bread diets were fed to 64 female Sprague-Dawley Albino rats for a period of 28 days. The retention of Ca, Fe and Zn was measured in plasma, femur and liver tissues of rats. The results showed that the feed intake and live body weight of the experimental animals incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Bread has always been an important component of the human nutrition and in many countries it constitutes the most important source of different nutrients such as proteins, fibres, minerals and vitamins (Thompkinson et al 2012;Ahmed et al 2011). During the last two decades, real trends toward healthy eating and developments of functional foods were noticed worldwide (Annapure et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bread has always been an important component of the human nutrition and in many countries it constitutes the most important source of different nutrients such as proteins, fibres, minerals and vitamins (Thompkinson et al 2012;Ahmed et al 2011). During the last two decades, real trends toward healthy eating and developments of functional foods were noticed worldwide (Annapure et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Food and Agriculture Organization of the United Nations (FAO 2012), apart soybean and rapeseed, sunflower seeds are among the world's most important oilseeds with a world production of ≅ 472 million tonnes in 2011/2012(FAO 2012. From nutritional point of view, sunflower seeds contain approximately 20 % crude proteins, whereas total protein content of the sunflower press cake is 30-50 % (Dorrell and Vick 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a study was developed to measure bioavailability and the extent of interaction among minerals such as calcium, iron and zinc, obtained from 72% extraction fortified wheat flour bread, using animal's model. The authors (Ahmed et al, 2012) found that the diet with zinc, in combination with calcium or iron, showed less zinc retention in plasma and liver, whereas the diet which contained zinc alone presented higher zinc levels in plasma and liver of rats. These data can be explained considering antagonistic Ca-Zn interactions, suggesting that higher dietary calcium can provide lower zinc absorption (Ahmed et al, 2012).…”
Section: Zinc Absorption In Animals and Its Inhibitors/promotersmentioning
confidence: 99%
“…Biofortified wheat flour in iron and zinc facilitates the absorption of these chemical elements in the intestinal mucosa (Khoshgoftarmanesh et al, 2010;Ahmed et al, 2012), yet some interactions among minerals might change their bioavailability (Ahmed et al, 2012). In this context, a study was developed to measure bioavailability and the extent of interaction among minerals such as calcium, iron and zinc, obtained from 72% extraction fortified wheat flour bread, using animal's model.…”
Section: Zinc Absorption In Animals and Its Inhibitors/promotersmentioning
confidence: 99%
“…O grupo dos lácteos foi o mais consumido em ambos os sexos (homens=54,3% e mulheres= 61,9%). Esse resultado é benéfico à amostra estudada por ser esse grupo fonte de proteína e de cálcio, nutrientes essenciais em diversas funções biológicas (AHMED et al, 2012).…”
unclassified